2019
DOI: 10.3389/fnhum.2019.00281
|View full text |Cite
|
Sign up to set email alerts
|

Expectation Gates Neural Facilitation of Emotional Words in Early Visual Areas

Abstract: The current study examined whether emotional expectations gate attention to emotional words in early visual cortex. Color cues informed about word valence and onset latency. We observed a stimulus-preceding negativity prior to the onset of cued words that was larger for negative than for neutral words. This indicates that in anticipation of emotional words more attention was allocated to them than to neutral words before target onset. During stimulus presentation the steady-state visual evoked potential (SSVEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Several studies reported that the visual cortex activation is linked to the processing of emotional information (Bekhtereva et al, 2015;Chen et al, 2015;Herbert, 2009;Frank et al, 2019;Keil et al, 2009;Sambuco et al, 2020;Schindler & Kissler, 2016;Trauer et al, 2019). A possibility is that emotionality is modulated by the anterior cortex and subcortical structures that send their modulation back to the visual cortex through the afferent pathway, resulting in an enhanced attentional engagement in the visual cortex (Keil et al, 2009).…”
Section: Positive Bias In L2 Contextmentioning
confidence: 99%
“…Several studies reported that the visual cortex activation is linked to the processing of emotional information (Bekhtereva et al, 2015;Chen et al, 2015;Herbert, 2009;Frank et al, 2019;Keil et al, 2009;Sambuco et al, 2020;Schindler & Kissler, 2016;Trauer et al, 2019). A possibility is that emotionality is modulated by the anterior cortex and subcortical structures that send their modulation back to the visual cortex through the afferent pathway, resulting in an enhanced attentional engagement in the visual cortex (Keil et al, 2009).…”
Section: Positive Bias In L2 Contextmentioning
confidence: 99%